TO DETERMINE THE IMPACT OF ERP IMPLEMENTATION IN IMPROVING THE SCM OPERATIONS IN MANUFACTURING - HASSAN ZOHAIB QURESHI; DR. MUHAMMAD ASIM; SALMAN MANZOOR (CenRaPS Journal of Social Sciences, 2020)
The research is carried out to determine the impact of ERP implementation in the improvement of the Supply chain in the manufacturing sector. The research undermines a detail investigation of How ERP is working to improve the performance of a firm. However, our research is quite specific with improving SCM performance. The identified problem for the research I basically related to process issues, control management issues etc. However, ERP has come up with solutions for it. Previous researches have clearly documented the fact that ERP is based on best practices and therefore, it being’s revolution to the firms. The research is carried out on a similar basis to determine how manufacturing firms with ERP can improve its SCM performance. In conclusion, the research identifies that manufacturing firms through ERP implementation can serve in leading the market, fulfilling the right demand, saving cost and improving operations.